An external sodium ion binding site controls allosteric gating in TRPV1 channels - Jara-Oseguera, Andres (eLife, 2016)
TRPV1 channels in sensory neurons are integrators of painful stimuli and heat, yet how they integrate diverse stimuli and sense temperature remains elusive. Here, we show that external sodium ions stabilize the TRPV1 channel in a closed state, such that removing the external ion leads to channel activation. In studying the underlying mechanism, we find that the temperature sensors in TRPV1 activate in two steps to favor opening, and that the binding of sodium to an extracellular site exerts allosteric control over temperature-sensor activation and opening of the pore. The binding of a tarantula toxin to the external pore also exerts control over temperature-sensor activation, whereas binding of vanilloids influences temperature-sensitivity by largely affecting the open/closed equilibrium. Our results reveal a fundamental role of the external pore in the allosteric control of TRPV1 channel gating and provide essential constraints for understanding how these channels can be tuned by diverse stimuli. DOI: http://dx.doi.org/10.7554/eLife.13356.001